Remission of Spontaneous Canine Tumors after Systemic Cellular Viroimmunotherapy - Cejalvo, Teresa; Perisé Barrios, Ana Judith; del Portillo, Isabel; Laborda, Eduardo; Rodríguez Milla, Miguel Ángel; Cubillo, Isabel; Vázquez, Fernando; Sardón Ruiz, David; Ramírez, Manuel; Alemany, Ramon; del Castillo Magan, Noemi; García Castro, Javier (My University, 2018)
Dogs with spontaneous tumors treated in veterinary hospitals offer an excellent oppor tunity for studyingimmunotherapies,including oncolytic viruses. Oncolytic viruses have advanced into the clinic as an intratumorally administered therapeutic;however,intravenous delivery has been hindered by neutralization in the blood. To circumvent this hurdle, mesen chymal stem cells have been used as a "Trojan horse." Here, we present the treatment of 27 canine patients with cancer with canine mesen chymal stem cells infected with ICOCAV17, a canine oncolytic adenovirus. No significant adverse effects were found. The response rate was 74%, with 14.8% showing complete responses, including total remissions of lung metastasis. We detected virus infection, stromal degeneration, and immune cell infiltration in tumor biopsies after 4 weeks of treatment. The increased presence of antiadenoviral antibodies in the peripheral blood of treated dogs did not appear to prevent the clinical benefit of this therapy. These dataindicate that oncolytic virus es loaded in mesenchymal stem cells represent an effective cancer immunotherapy